BIOMOLECULES CONTAINED POLYETHYLENE TO DEGRADATION BY MICRO-ORGANISMS - Lazras, Ashadeepika (International Journal of Research -GRANTHAALAYAH, 2015)
The mechanisms of degradation of polyethylene films are various ways such in soil containing microbes. The culture micro-organisms with suitable media such as SDA and YEMA contained some biochemical such as Starch, Cellulose and Plant Extract for both fungi and agro-bacteria.The biochemical substrate has increased the degradation efficiency. In this investigation highest degradation of polythene at 59.69% by micro-organisms in which contained MPE compared to other.